Kajian Psikolinguistik: Gangguan Berbahasa Tokoh Angel dalam Film Sebuah Lagu untuk Tuhan - Amay Lanjar Wulandari; Ilya Zulfadilla; Adristi Afdal; Fatmawati Fatmawati; Rhani Febria (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This research was conducted to look at language abnormalities in the character Angel in the film A Song for God. In addition, this research was conducted to find out how Angel character communicates with the people around her. The method used in this research is descriptive qualitative analysis. The technique used is the technique of observing and noting. The data in this study are the words or sentences uttered by the character Angel in the film A Song for God, while the source of the data in this study is the film A Song for God. The results of the study found that the words or sentences spoken by Angel sounded nasal and unclear. When viewed from phonological utterances, there are several dominant phonemes that sound unclear, such as phonemes /k/, /n/, /d/, /g/, /t/, /ai/, /i/, /y/, and the word "create" sounds like "snap". In her daily life, the character Angel uses sign language and reads lip language and pays attention to someone's body movements when communicating.